RETRACTION Yanti, N., Selviani, I.., Supriatna, E.., Nofrizal, D.., Purba, P. H., Lubis, H. Y.., Nurbait, S.., Putro, D. E., Ismoko, A. P.., Wahyuni, D., Suryadi, D., & Suganda, M. A. (2024). Eficacia del entrenamiento pliométrico en balonmano: impacto en la potencia y velocidad de lanzamiento (Effectiveness of plyometric training in handball: impact on throwing power and speed)Effectiveness of plyometric training in handball: impact on throwing power and speed). Retos, 58, 643–649. https://doi.org/10.47197/retos.v58.103521 - RETOS, RETOS (Retos, 2025)
Yanti, N., Selviani, I.., Supriatna, E.., Nofrizal, D.., Purba, P. H., Lubis, H. Y.., Nurbait, S.., Putro, D. E., Ismoko, A. P.., Wahyuni, D., Suryadi, D., & Suganda, M. A. (2024). Eficacia del entrenamiento pliométrico en balonmano: impacto en la potencia y velocidad de lanzamiento (Effectiveness of plyometric training in handball: impact on throwing power and speed)Effectiveness of plyometric training in handball: impact on throwing power and speed). Retos, 58, 643–649. https://doi.org/10.47197/retos.v58.103521Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Autores en el Word del artículo enviado a revisión: 9Autores en el PDF publicado con los autores modificados: 12Diferencia de los autores entre ambos momentos: +9 y -3 (Añadidos: Iit Selviani, Eka Supriatna, Dedi Nofrizal, Pangondian Hotliber Purba, Hafiz Yazid Lubis, Syifa Nurbait, Danang Endarto Putro, Anung Probo Ismoko, Dewi Wahyuni. Eliminado: Nugroho Susanto, Putra Sastaman B, Sandey Tantra Paramitha, Ardi Nusri, Dilli Dwi Kuswoyo, Ahmad Nasrulloh)